THE INFLUENCE OF SORGHUM FLOUR SUBSTITUTION IN FARFALLE SENSORIAL CHARACTERISTICS - Sugijono, Nurul Wahidah (Prosiding Pendidikan Teknik Boga Busana, 2020)
This study substituted farfalle (a ribbon or butterfly paste product) with sorghum flour. Farfalle is made from sorghum flour, flour, salt, water, eggs, olive oil, basil leaves. Farfalle was developed with a type of research and development, a model approach to define, design, develop and disseminate (4D) and a T-test. The research phase is validation I with 2 food experts, validation II with 2 food experts, test preferences with 30 semi-trained panelists or semester II students of the Yogyakarta Technical Education Study program and acceptance tests with a minimum of 50 untrained panelists or visitors to the final project exhibition. Collecting data with questionnaires or product feasibility forms in a sensory manner to analyze color, aroma, texture, taste and overall acceptance. Based on the results of the study, the best farfalle was determined with a composition of 18.60% sorghum flour, wheat flour 43.41%, water 35.66%, salt 0.47%, angkak 0.47% and mustard greens 1.40%. Keywords: Farfalle, sorghum